Microbial Mats in Silicilastic Depositional Systems Through Time 2012
DOI: 10.2110/sepmsp.101.139
|View full text |Cite
|
Sign up to set email alerts
|

Criteria For Distinguishing Microbial Mats and Earths

Abstract: Microbial earths are communities of microscopic organisms living in well-drained soil. Unlike aquatic microbial mats and stromatolites, microbial earths are sheltered from ultraviolet radiation, desiccation, and other surficial hazards within soil cracks and grain interstices. Currently, such ecosystems are best known in small areas of unusually cold, hot, or saline soils unfavorable to multicellular plants and animals. During the Precambrian, microbial earths may have been more widespread, but few examples ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 132 publications
1
24
0
1
Order By: Relevance
“…Nevertheless, our results support the presence of significant microbial land colonization by 2.76 Ga, as previously documented by (Rye and Holland, 2000;Stueken et al, 2012;Watanabe et al, 2000Watanabe et al, , 2004. Possibly, the occurrence of organic material in the MR#1 and MR#2 paleosols could reflect a significant production of organic acids through microbial activity, which may have also participated in the leaching of ferric oxides (Ohmoto, 1996;Retallack, 2012).…”
Section: Organic Carbonsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, our results support the presence of significant microbial land colonization by 2.76 Ga, as previously documented by (Rye and Holland, 2000;Stueken et al, 2012;Watanabe et al, 2000Watanabe et al, , 2004. Possibly, the occurrence of organic material in the MR#1 and MR#2 paleosols could reflect a significant production of organic acids through microbial activity, which may have also participated in the leaching of ferric oxides (Ohmoto, 1996;Retallack, 2012).…”
Section: Organic Carbonsupporting
confidence: 89%
“…The presence of terrestrial methanotrophs, suggested by the occurrence of 13 C-depleted carbonaceous material atop the diaspore-pyrophyllite boudins (see Section 9), may be further support for oxidizing conditions during weathering. Also, the presence of microbial activity may have been responsible for significant leaching of ferric oxides through the production of organic acids (Ohmoto, 1996;Retallack, 2012). The net gain of Al is best attributed to lateral migration of aluminum in soil profiles as documented in modern, intensely weathered bauxites (Valeton, 1972).…”
Section: Smectite-barite-sphene-fe-sericite (Mr#1)mentioning
confidence: 99%
“…Aunque existen análogos fósiles de CGC (Simpson et al, 2010;Beraldi-Campesi et al, 2011;Retallack, 2009Retallack, , 2011Sheldon, 2012), no se sabe cuál fue su composición microbiana. Comparativamente, cualquier costra biológica del suelo es menos resistente que los tapetes microbianos Figura 2.…”
Section: Funcionamiento De Los Ecosistemas Terrestres Primitivosunclassified
“…(2012). Abundant life, at least at the microbial level, is the most likely explanation for many documented palaeosol features: surficial enrichment in clay, segregation of calcite nodules and gypsum crystals, and depletion of alkali and alkaline earth elements and phosphorus within the palaeosol profiles (Retallack 2008, 2012 a ).…”
mentioning
confidence: 99%
“…2012). Funisia and Coronacollina may also have been soil organisms because they are found on cracked surfaces (‘old elephant skin’) characteristic of Ediacaran soil crusts (Retallack 2012 a , b ). Features of the fossils considered relict bedding by Jago et al .…”
mentioning
confidence: 99%